Hamburg and the enlarged EEC - Hans Fahning (Intereconomics, 1973)
Hamburg's trade has profited from the dynamic effects of the European Common Market. In the following interview Dr Fahning, Director of the Hamburgische Landesbank-Girozentrale, gives his views on the importance of the EEC enlargement for the Hanseatic City.
Keywords: 330; Germany